Human Rights: Experiences and Educational Practices (International Journal of Scientific Research and Management (IJSRM), 2024)
Human rights, therefore, are indispensable freedoms that accrue to every human being, irrespective of citizenship, ethnic background, or other characteristics. It is true that all these rights are known globally, but the chances of people realizing and enjoying them can differ significantly depending on the region and specific society. These gaps in knowledge are considered in this research article by discussing the various, differentiated experiences in regard to human rights, more specifically by pointing to incidents of human rights’ abuse and improvement across different regions. Moreover, the given article explores the centrality of education in raising awareness and cherishing human rights.HRE, as a part of educational practices, can raise awareness, foster empathy, and, thereby, actively contribute to individuals’ ability to stand up for themselves and others. Therefore, through teaching and learning human rights, the incorporation of human rights topics in education curriculum, teaching critical thinking, and establishing values for empathy, HRE seeks to transform society into one that respects and protects the human rights of every individual. This paper explores the historical past, various problems in present society, as well as the experience of HRE implementation that occurred in different countries at different times, its outcomes, and perspectives for further transformations in society.In the last place, the author presents the recommendations that can help improve HRE, discussing the role of international support, advocacy, and efficient teacher training. This way, HRE helps build a desirable future for humanity’s generations to come by preparing them for the combating of human rights issues.